Implementation SCUN (National Single Account System) in institutions national budget (2014)
This trial is the result of the proposed implementation SCUN (Unique Account System National) in financial sub DPS (Department for Social Prosperity) with the experience of the pilot applied in 2014, was selected this topic because which is of great importance because the entities that make up the general budget of the nation should use this system through SIIF (Integrated Financial Information System), this occasion to the revenues, transfers and turns that these entities are handled under the procedures Teaching guidelines and the Ministry of Finance through the National Treasury Management (DTN) and parameters issued by the General Accounting Office.